1996
DOI: 10.1103/physrevlett.76.1603
|View full text |Cite
|
Sign up to set email alerts
|

Wigner Random Banded Matrices with Sparse Structure: Local Spectral Density of States

Abstract: Random banded matrices with linearly increasing diagonal elements are recently considered as an attractive model for complex nuclei and atoms. Apart from early papers by Wigner [1] there were no analytical studies on the subject. In this letter we present analytical and numerical results for local spectral density of states (LDOS) for more general case of matrices with a sparsity inside the band. The crossover from the semicircle form of LDOS to that given by the Breit-Wigner formula is studied in detail.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
182
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(191 citation statements)
references
References 23 publications
(38 reference statements)
7
182
0
Order By: Relevance
“…(7) with Γ = 2πV 2 ρ, provided the eigenstates are localized within the band: Γ < Db. Recently this result has been derived for sparse matrices with a diffuse band [39]. The BW spreading also emerges in the well-known nuclear physics model of a state interacting with a large set of states with ρ = const by means of a constant or weakly fluctuating matrix element [5].…”
Section: Chaotic Eigenstatesmentioning
confidence: 99%
“…(7) with Γ = 2πV 2 ρ, provided the eigenstates are localized within the band: Γ < Db. Recently this result has been derived for sparse matrices with a diffuse band [39]. The BW spreading also emerges in the well-known nuclear physics model of a state interacting with a large set of states with ρ = const by means of a constant or weakly fluctuating matrix element [5].…”
Section: Chaotic Eigenstatesmentioning
confidence: 99%
“…In particular the width Γ gives an energy scale at which the level statistics, for example the number variance Σ 2 (E), changes behavior from the WignerDyson to the Poisson case [9]. It has been also shown that the Breit-Wigner distribution appears in the case of sparse random matrices with preferential basis [10].While the properties of the Breit-Wigner distribution are well understood in random matrix models, the problem of real interacting finite many-body fermionic systems was much less investigated. Indeed, in the latter case the nature of the two-body interaction should be taken into account, since it gives certain restrictions on the structure of matrix elements.…”
mentioning
confidence: 99%
“…In particular the width Γ gives an energy scale at which the level statistics, for example the number variance Σ 2 (E), changes behavior from the WignerDyson to the Poisson case [9]. It has been also shown that the Breit-Wigner distribution appears in the case of sparse random matrices with preferential basis [10].…”
mentioning
confidence: 99%
“…These methods include banded random matrix models [3,17,18,19], models of a single-level with constant couplings to a "picketfence" spectrum [4,20], and perturbative techniques with partial summations over diagrams to infinite order [21]. Under inequivalent assumptions these approaches affirm a generic Breit-Wigner shape for the LDOS profile,…”
mentioning
confidence: 99%
“…1 applies when a given quantized classically chaotic model is subjected to a perturbation of interest. From the BGS conjecture [24] and studies of (banded) random matrix models [3,17,18,19], it is generally expected that for fully chaotic models with generic perturbations Eq. 1 applies with,…”
mentioning
confidence: 99%